Nuevos descubrimientos sobre Ambrósio Fernandes Brandão, autor más probable del Diálogo das Grandezas do Brasil de 1618, en relación a su “cripto-judaísmo” y a su especial relación con la India y con la monarquía compuesta de los Habsburgo españoles - José Manuel Santos Pérez (Caravelle)
New and important discoveries about the Diálogo das Grandezas do Brasil, an anonymous work written in 1618, and its most probable author, the New Christian Ambrósio Fernandes Brandão, come to light from documents recently found in the Archivo General de Simancas in Spain and the Arquivo Nacional da Torre do Tombo in Portugal. The present text discusses these new findings that shed light on Brandão’s biography.